Historical perspective of international humanitarian law: Conventional Law, emerging issues - Archibong, James E.; Ugbe, Rose Ohiama (Edelweiss Applied Science and Technology, 2024)
When there is an armed conflict, international humanitarian law (IHL) is applicable. It controls the means and tactics of combat while also protecting victims of armed conflict. The law has been around since antiquity, but the current version was created in 1864. Since then, as armed conflicts have become more complicated and sophisticated, the law has changed accordingly. However, there are a lot of additional advances that aren't covered by IHL. Law, which is falling behind in many areas, is not keeping up with developments in armed conflicts. Many of the issues related to modern armed conflicts are beyond the purview of existing IHL. Among the difficulties are the creation of autonomous weaponry, the rise of private military contractors, the use of sexual assault as a weapon of mass destruction, and the expansion of armed factions. The challenge of controlling warfare is made more difficult by the lack of or insufficiency of legal and regulatory structures. To address these issues, this work suggests reviewing the Additional Protocols and the Geneva Conventions.